(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
This article focuses on the formation of emotional intelligence in adolescence and its psychological characteristics. Interrelated aspects of emotional-volitional and cognitive processes in adolescence are studied and the levels of emotional intelligence are described separately